Response of the pulp of dogs to capping with mineral trioxide aggregate or a calcium hydroxide cement - Faraco, I. M.; Holland, R. (Munksgaard Int Publ Ltd, 2001)
This study was conducted to observe the response of dogs' dental pulp to mineral trioxide aggregate (MTA) and a calcium hydroxide cement when used as pulp capping materials. After the pulps of 30 teeth were exposed, they were capped with either MTA or a calcium hydroxide cement. Histological analysis was performed 2 months after treatment. Results showed a healing process with complete tubular dentin bridge formation and no inflammation in any of the pulps capped with MTA. on the other hand, only five specimens from the calcium hydroxide cement group formed a complete dentin bridge. In this experimental group, pulp inflammation was observed in all but three cases. In conclusion, MTA exhibited better results than the calcium hydroxide cement for the capping of the pulp in dogs.
Keywords: dental pulp capping; pulpal response; mineral trioxide aggregate